Using Foliar Application of Fe and GA3 to Improve Growth of Two Olive cv. (Olea europaea ) Transplants. - Al-Bamarny, Sarfaraz F.; Abdulrhman, Amira S. (Science Journal of University of Zakho, 2018)
This investigation was carried out in the lath house of the nursery of Malta station/ Duhok. Kurdistan region, Iraq. During the growing season of 2017, to study the effect of the different concentrations of Fe (0, 10 and 20 mg.L -1) and GA3 (0 , 500 and 1000 mg.L-1) on vegetative growth, roots length and leaves nutrients content of one year old of two olive cultivars (Nebali and Bashike) transplantings. The results appear that Nebali cultivar significantly dominated in stem length (cm), stem diameter(mm), branch length(cm), leaves number, root length(cm), N(%), K(%), P(%) and Fe(mg.L-1), Baeshike cultivar dominate in leaf area (cm2), stem length(cm) , shoot root ratio(%), root length(cm) and K (%) were significantly increased with the increase the GA3 to 1000 mg.L-1. Foliar application of GA3 at 500 mg.L-1 significantly increased branch length (cm) and P (%). The transplants sprayed with the Fe in 10 mg.L-1 only significantly effect on the Fe % content but spray transplants with the Fe at 20 mg.L-1 had significantly affected on stem diameter(mm), leave number root length(cm) and N(%). Most of the interactions (cultivar × Fe and cultivar × GA3) showed significant effects on the most studied characteristics.